Answer:
bottom 2 shapes
Step-by-step explanation:
Answer:
171
Step-by-step explanation:
fbgetjmnryjnmyjnmryjnhm
Answer:
-20 = 0
Step-by-step explanation:
-8 (6 + x) + 4 (2x + 7) = 0
-48 - 8x + 8x + 28 = 0
-20 = 0
Answer:
Step-by-step explanation:
Figure 1
- 3 = 4 - 1 = 2² - 1 = (1 + 1)² - 1
Figure 2
- 8 = 9 - 1 = 3² - 1 = (2 + 1)² - 1
Figure 3
- 15 = 16 - 1 = 4² - 1 = (3 + 1)² - 1
<u>The function is:</u>
Answer:
Step-by-step explanation:
Use Pythagorean theorem.
Hypotenuse² = base² + altitude²
5) x² = 12² + 6²
= 144 + 36
x² = 180
x = √180
x = 13.42 ft
6) 25² = x² + 19²
625 = x² + 361
625 - 361 = x²
x² = 264
x = √264
x = 16.25 m
7) x² = 7² + 576
= 49 + 576
= 625
x = √625
x = 25 in
8) 2.5² = 2²+ x²
6.25 = 4 + x²
6.25 - 4 = x²
x² = 2.25
x = √2.25
x = 1.5 yd